2010
DOI: 10.1111/j.1467-9779.2010.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Market Design: A Field Experiment at Google Answers

Abstract: In a field experiment at Google Answers, we investigate the performance of price-based online knowledge markets by systematically manipulating prices. Specifically, we study the effects of price, tip, and a reputation system on both an answerer's effort and answer quality by posting real reference questions from the Internet Public Library on Google Answers under different pricing schemes. We find that a higher price leads to a significantly longer, but not better, answer, while an answerer with a higher reput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(81 citation statements)
references
References 24 publications
3
78
0
Order By: Relevance
“…Knowledge market systems foster knowledge sharing using a dynamic price mechanism within organisations and all benefits of knowledge sharing can be captured by monetary mechanisms. Although knowledge markets are designed by virtual monetary mechanism, other extrinsic rewards like as reputation incentive are used for participant engagement (Chen et al, 2010). Internal knowledge market systems rank medium on the interaction dimension.…”
Section: Internal Knowledge Market Systemmentioning
confidence: 99%
“…Knowledge market systems foster knowledge sharing using a dynamic price mechanism within organisations and all benefits of knowledge sharing can be captured by monetary mechanisms. Although knowledge markets are designed by virtual monetary mechanism, other extrinsic rewards like as reputation incentive are used for participant engagement (Chen et al, 2010). Internal knowledge market systems rank medium on the interaction dimension.…”
Section: Internal Knowledge Market Systemmentioning
confidence: 99%
“…Using data collected from Yelp.com, Wang (2010) argues that social image and reviews' productivities are positively correlated. Alternative ways of motivating agents are also explored in the work of Bénabou and Tirole (2003), Ariely et al (2009), Chen at al (2010b.…”
Section: Introductionmentioning
confidence: 99%
“…Chen, Ho, and Kim (2010), conceptualized Google Answers as a knowledge market, and while the price offered for answering a question was a significant factor in answer quality, they reported that the reputation of an answerer also helped lower barriers to Q&A transactions. Shachaf and Rosenbaum (2009) propose a Socio-Technical Interaction Network (STIN) framework approach as a conceptual lens for SQA.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Answers users were judged to be as good or better than those provided by experts or professionals on other sites. Similarly, Chen, Ho, and Kim (2010) investigated the performance of price-based Q&A systems in their study of Google Answers. In contrast to Harper et al, they found that offering a higher price for an answer led to a significantly longer, but not better, answer, and that answerers with a higher reputation provide significantly better answers.…”
Section: Answer Classification and Quality Evaluationmentioning
confidence: 99%